2015
DOI: 10.1021/am506793b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Gas Adsorption Selectivity in IRMOF-8 Using Molecular Simulation

Abstract: Grand canonical Monte Carlo simulations were used to explore the adsorption behavior of methane, ethane, ethylene, and carbon dioxide in isoreticular metal-organic frameworks, IRMOF-1, noninterpenetrated IRMOF-8, and interpenetrated IRMOF-8. The simulated isotherms are compared with experimentally measured isotherms, when available, and a good agreement is observed. In the case of IRMOF-8, the agreement is much better for the interpenetrated model than for the noninterpenetrated model, suggesting that the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 65 publications
(191 reference statements)
3
67
3
3
Order By: Relevance
“…Although DREIDING has been shown to significantly over-estimate methane adsorption when compared to experiment in ZIF-8 [23], very good agreement was observed in the case of UiO-66(Zr) [22] (~9-20% over-estimation for θ < 0.5) and in the present work, while simulations in IRMOF-1 and IRMOF-6 [12] and in IRMOF-8 [48] found excellent quantitative agreement with experiment (5-10% difference when averaged over the full isotherm). While there are too many variables to fully rationalise these apparent differences in quantitative agreement (e.g.…”
Section: Prediction Of Adsorption Isothermssupporting
confidence: 74%
See 3 more Smart Citations
“…Although DREIDING has been shown to significantly over-estimate methane adsorption when compared to experiment in ZIF-8 [23], very good agreement was observed in the case of UiO-66(Zr) [22] (~9-20% over-estimation for θ < 0.5) and in the present work, while simulations in IRMOF-1 and IRMOF-6 [12] and in IRMOF-8 [48] found excellent quantitative agreement with experiment (5-10% difference when averaged over the full isotherm). While there are too many variables to fully rationalise these apparent differences in quantitative agreement (e.g.…”
Section: Prediction Of Adsorption Isothermssupporting
confidence: 74%
“…1) are representative of the trends observed in all seven systems. As has been noted previously in the case of covalent organic frameworks [20] and IRMOF-8 [48], UFF tends to significantly over-estimate adsorbed amounts compared to DREIDING, by between 15 and 50%. The OPLS-AA force field performs very similarly to UFF, over-estimating compared to DREIDING by between 8% and 40%.…”
Section: Prediction Of Adsorption Isothermssupporting
confidence: 62%
See 2 more Smart Citations
“…Pillai et al (Pillai et al, 2015) recently used GCMC simulations to explore C 2 H 6 /C 2 H 4 separation in two isoreticular MOFs, non-interpenetrated IRMOF-8 and interpenetrated IRMOF-8. Their results showed that C 2 H 6 selectivities are less than 2 at 10 bar, 298 K. (Chung et al, 2014) was used in addition to 45 well-known MOFs taken from our previous study (Sezginel et al, 2015) to cover widely studied subfamilies such as ZIFs, covalent organic frameworks (COFs), bioMOFs.…”
Section: Introductionmentioning
confidence: 99%